A site selection decision framework for offshore wind-powered hydrogen production infrastructure - Kumar, Sumit; Arzaghi, Ehsan; Baalisampang, Til; Garaniya, Vikram; Abbassi, Rouzbeh (Volume 8: Ocean Renewable Energy, 2023)
This study develops a novel and robust multi-criteria decision-making (MCDM) framework to determine the optimal offshore location for producing green hydrogen and a series of infrastructure planning measures. A range of factors, including technical, economic, environmental and safety, that govern the life cycle of offshore hydrogen facilities are incorporated into the model. An offshore wind-powered hydrogen system in the Bass Strait region of Australia has been considered as a case study to show the application of the developed framework along with the synergic benefits to nearby offshore industries. A GIS spatial analysis tool is utilized to rule out the unfeasible/constrained areas in compliance with national and international guidelines. TOPSIS MCDM technique is applied to weigh the criteria and rank the alternative locations. Based on hydrogen production capacity, cost and availability, various locations are ranked, illustrating their suitability. The developed framework demonstrated its high effectiveness in terms of extensive applicability and ease of usage. The outcomes of this investigation will assist the researchers and infrastructure developers in establishing and executing effective planning for offshore site selection in the largely uncertain and harsh ocean environment.